The Effect of Enviromental Performance, Company's Characteristics and Good Corporate Governance (GCG) on Environmental Disclosure (Empirical Study of Mining Companies Listed on The Indonesia Stock Exchange (IDX)2015-2019) - Tita Nurvita; Aloysius Priambodo (Universitas Muhammadiyah Jakarta, 2022)
The study aims to determine the effect of environmental performance, company’s characteristics (company size, company age) and good corporate governance (GCG) (Board of Commissioners, Independent Commissioners and Audit Committee) on environmental disclosure. The population in this study are mining companies published on the Indonesia Stock Exchange (IDX) for the 2015-2019 period. The analysis carried out in this research is descriptive statistical test, panel data testing, classical assumption test and hypothesis testing. The results indicate that the Environmental Performance variable and the Firm Size variable have a positive effect on Environmental Disclosure. While the variables of company age, Board of Commissioners, Independent Commissioner and Audit Committee have no effect on Environmental Disclosure.